Effects of religious orientation and state secularism on pre-implantation genetic diagnosis. Issue 8 (August 2020) - Hichy, Zira; Sciacca, Federica; Di Marco, Graziella; De Pasquale, Concetta
Abstract: This study aimed to test the associations of religious orientation (extrinsic, intrinsic, and quest) and secularism of state with individuals' attitudes towards the pre-implantation genetic diagnosis of embryos. Moreover, we tested the mediating effects of secularism of state on the relationship between religious orientations and attitudes towards this issue related to embryos. Participants were 312 Catholic Italians that completed a questionnaire containing measures of investigated constructs. Results showed that attitude towards pre-implantation genetic diagnosis negatively correlated with intrinsic religious orientation and positively with extrinsic religious orientation and secularism. Moreover, results indicated that secularism mediated the relationship between extrinsic and intrinsic orientation and attitude towards pre-implantation genetic diagnosis. Taking together these results indicate that real endorsement with religion is associated with the refusal of pre-implantation genetic diagnosis because intrinsic religious orientation is related to the desire for state laws to follow religious principles; on the other hand, the use of religion for utilitarian reasons is associated to the acceptance of pre-implantation genetic diagnosis in order to have a religious state and then maintain Catholics' privileges. Abstract : Psychology; State secularism; Religious orientation; Pre-implantation genetic diagnosis